CD47 as a promising therapeutic target in oncology - Hai, Zhao; Shucheng, Che; Junwei, Ma; Hongwei, Xie; Zhiyong, Yan (Frontiers in Immunology, 2022)
CD47 is ubiquitously expressed on the surface of cells and plays a critical role in self-recognition. By interacting with SIRPα, TSP-1 and integrins, CD47 modulates cellular phagocytosis by macrophages, determines life span of individual erythrocytes, regulates activation of immune cells, and manipulates synaptic pruning during neuronal development. As such, CD47 has recently be regarded as one of novel innate checkpoint receptor targets for cancer immunotherapy. In this review, we will discuss increasing awareness about the diverse functions of CD47 and its role in immune system homeostasis. Then we will discuss its potential therapeutic roles against cancer and outlines the possible future research directions of CD47- based therapeutics against cancer.